Security challenges in automotive hardware/software architecture design - Sagstetter, Florian (2013)
This paper is an introduction to security challenges for the design of automotive hardware/software architectures. State-of-the-art automotive architectures are highly heterogeneous and complex systems that rely on distributed functions based on electronics and software. As cars are getting more connected with their environment, the vulnerability to attacks is rapidly growing. Examples for such wireless communication are keyless entry systems, WiFi, or Bluetooth. Despite this increasing vulnerability, the design of automotive architectures is still mainly driven by safety and cost issues rather than security. In this paper, we present potential threats and vulnerabilities, and outline upcoming security challenges in automotive architectures. In particular, we discuss the challenges arising in electric vehicles, like the vulnerability to attacks involving tampering with the battery safety. Finally, we discuss future automotive architectures based on Ethernet/IP and how formal verification methods might be used to increase their security.